To find the solution to the system of equations given by:
- \( y = -2x + 3 \)
- \( y = 5x - 4 \)
we can set the two equations equal to each other since both are equal to \( y \):
\[ -2x + 3 = 5x - 4 \]
Now, we will solve for \( x \):
- Add \( 2x \) to both sides:
\[ 3 = 7x - 4 \]
- Add \( 4 \) to both sides:
\[ 7 = 7x \]
- Divide both sides by \( 7 \):
\[ x = 1 \]
Now that we have \( x \), we can substitute it back into either of the original equations to find \( y \). Using the first equation:
\[ y = -2(1) + 3 = -2 + 3 = 1 \]
Thus, the solution to the system of equations is:
\[ (x, y) = (1, 1) \]
So, the point of intersection (the solution to the system) is \( (1, 1) \).